Japan's Network Economy: Structure, Persistence, and ChangeJapan's Network Economy: Structure, Persistence, and Change, by LincolnJames R. and GerlachMichael L.. Cambridge: Cambridge University Press, 2004. - Parkhe, Arvind (Academy of Management Review, 2007)
The article presents a review of a book entitled ?Japan's Network Economy: Structure, Persistence, and Change,? James R. Lincoln and Michael L. Gerlach.